DATA COMPRESSION AND PANORAMIC IMAGES FORMATION IN UAV MILITARY TV-MONITORING SYSTEM - Cristian-Valentin, Eremia; Giorgian, Neculoiu; Oana, Grigoriu; Oboukhova, Natalia; МоtukоАlexandr (European Scientific Journal, ESJ, 2013)
UAVs are unmanned aerial vehicles. UAVs with qualities of robots are called "drones" and are used mostly for acquisition and transmission of TV image for observation missions in enemy territories or guarding of objects and large land areas. TV images acquired by these drones are converted into compressed data and then transmitted to the ground via radio - communications. If the monitored area is large or the observed object is big, then more drones buy pieces from the total image. The paper shows the results of the analysis of experimental data compression standard methods and Method of panoramic images formation in the conditions of initial frames with low detail is offered. Method saves perspective of base frame.